2005
DOI: 10.2214/ajr.184.3.01840984
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid Dysplasia: Incidence and Association with Posterior Labral Tears as Evaluated on MRI

Abstract: In our study population, we found that moderate to severe glenoid dysplasia is not a rare entity as seen on MRI, with an incidence of 14.3%. Furthermore, we found that there is a statistically significant increase in the incidence of posterior labral tears associated with shoulders with moderate or severe glenoid dysplasia compared with those shoulders with no dysplasia or mild dysplasia as evaluated on MRI. Even when the mild cases were included, the incidence of posterior labral tears was significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 10 publications
1
50
0
1
Order By: Relevance
“…In patients with symptomatic labral pathology, surgical management may consist of debridement of hypertrophic tissue or repair of associated tears (13), which may be augmented by bony reconstruction utilizing osteotomy or grafting to restore articular anatomy as indicated (8,13). However, there is no standard association between bony and soft tissue abnormalities in patients with glenoid hypoplasia, and the spectrum of labral pathology may range from intrasubstance tears to complete detachment of the labrum from the glenoid (5,13). Only two cases of perilabral cyst formation related to glenoid hypoplasia have been previously reported in the literature (13).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with symptomatic labral pathology, surgical management may consist of debridement of hypertrophic tissue or repair of associated tears (13), which may be augmented by bony reconstruction utilizing osteotomy or grafting to restore articular anatomy as indicated (8,13). However, there is no standard association between bony and soft tissue abnormalities in patients with glenoid hypoplasia, and the spectrum of labral pathology may range from intrasubstance tears to complete detachment of the labrum from the glenoid (5,13). Only two cases of perilabral cyst formation related to glenoid hypoplasia have been previously reported in the literature (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that a hypoplastic glenoid is more susceptible to injury from such forces considering the vulnerability of the hypertrophied posterior labrum. 2,12 The conservative approach to glenoid hypoplasia consists of a physician-directed physical therapy program for rehabilitation and strengthening of the scapular stabilizers, rotator cuff, and deltoid muscles. 1,3 Further conservative care to address associated instability or internal joint derangement should be considered on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%
“…By examining 98 consecutive MRI arthrograms, Harper et al (2005) found 14.3% cases of moderate or severe dysplasia, but only 60.2% of strictly normal cases. In the latter group, 10.7% posterior labral tears were identified, although there were 33.3% in the dysplastic group.…”
Section: Minor Dysplasiamentioning
confidence: 94%
“…Such variability supports the idea that shoulder stability depends not only on bone architecture, but also on biomechanical equilibrium among the soft tissues of the region. Furthermore, in cases of excessive retroversion, relative compensation develops through localised hypertrophy of articular cartilage and the labrum, revealed by MRI (Harper et al, 2005). In addition to a study of shoulder instability, shoulder replacement requires great accuracy in measurements.…”
Section: Measuring Glenoid Retroversionmentioning
confidence: 99%
See 1 more Smart Citation